Population Transfer in a Gold-Nanoparticle-Coupled Λ-Type Quantum System Using Lewis-Riesenfeld Invariant-Based Shortcuts - mingjie lin; Yongbo Xiao; RenDi Luo; Wei Liu; Jingrong Zheng; Changshui Chen (Physica Scripta, 2026)
Abstract Lewis-Riesenfeld (LR) invariant-based inverse engineering is applied to a L -type quantum system coupled to a gold nanoparticle, and three auxiliary-angle paths satisfying the same boundary conditions are constructed. By incorporating the local-field modifications and spontaneous-emission decay rates induced by the metal nanoparticle (MNP), the density-matrix equations are solved to compare the final target-state populations of the three LR paths and conventional stimulated Raman adiabatic passage (STIRAP) under different quantum-system-metal-nanoparticle (QS-MNP) distances, free-space decay rates, Rabi frequencies, and polarization configurations. The results show that, under the first polarization configuration, the a2 path maintains a lower intermediate-state population and yields a high and stable final target-state population over most of the parameter range. Under the second polarization configuration, conventional STIRAP yields a higher final target-state population in some parameter regions. These results indicate that the final target-state population is affected by both opticalfield-driven coherent transfer and spontaneous emission, and that the choice of LR path should be evaluated by considering the intermediate-state population together with the modifications induced by the plasmonic environment.